Problem solving, abstraction, and design using C++ - Friedman, Frank L.; Koffman, Elliot B. (Boston Pearson, 2011)
This book presents and reinforces basic principles of software engineering design and object-oriented programming concepts while introducing the C++ programming language. The hallmark feature of this book is the Software Development Method that is introduced in the first chapter and carried throughout in the case studies presented.
Index.: p.885-903
Keywords: Công nghệ thông tin